Field Trials Indicating the Potential of Abutilon Theophrasti (Medic.) As A New Fibre Crop in Southwest Germany - Scheliga, Maria; Brand, Urs; Türk, Oliver; Gruber, Sabine; Petersen, Jan (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
Natural fibre based composites are being used more frequently in the automotive industry because of their positive characteristics. Fibres currently used and mostly imported to Europe do not sufficiently meet all the demands for natural fibres. As a new fibre plant velvetleaf (Abutilon theophrasti) has been taken into consideration. However, there is no knowledge about the cultivation of velvetleaf in Europe. Four field trials in southwest Germany were set up to investigate the potential of fibre yield in a temperate climate. The factors crop density, nitrogen fertilization, accessions, and different harvesting dates were tested. Across all experiments fibre yield ranged from 0.4 to 1.5 t ha-1 dry matter. The highest yields were achieved with a crop density of 30 plants m-2, and with N fertilization of 100-150 kg N ha-1 for the accession ‘Herbiseed’. For highest fibre yield, the date of harvest should be at the beginning of maturity. This study provides first insights into possibility and variation of cultivating velvetleaf and suggests adequate fibre yield when cultivated in proper plant density and appropriate accession. However, before the plant can be implemented as a new crop, more research on fibre quality and breeding activity to improve agronomic factors is required.